Jordanian Community People's Knowledge of and Attitudes Toward Dementia - Asem Abdalrahim PhD; Khaled Mohammad Alamoush MSN; Mohammed ALBashtawy PhD; Shaher H. Hamaideh PhD; Khitam Ibrahem Mohammad PhD, MSN, RN; Abdullah Alkhawaldeh PhD; Manar Alazzam PhD; Nisser Alhroub PhD; Mohammad Suliman PhD; Bayan ALBashtawy MD (SAGE Publishing, 2023)
Introduction Limited research exists on the knowledge and attitudes of Jordanian community residents toward people with dementia (PwD). As the prevalence of dementia is anticipated to increase, there is a critical need for informed knowledge and positive attitudes toward dementia in the Jordanian community. Objectives This study aimed to evaluate people's knowledge of and attitudes toward PwD and identify the predictors of dementia knowledge and attitudes. Methods The study employed a cross-sectional research design and utilized a self-administered questionnaire as the primary data collection method. The study employed the Alzheimer's Disease Knowledge Scale (ADKS) to evaluate the knowledge of the participants, and the Dementia Attitudes Scale (DAS) was utilized to assess their attitudes in the Jordanian community. Multiple regression analysis was performed to find relevant factors influencing knowledge of and attitude toward dementia. Results The study's 346 participants revealed limited knowledge about dementia, with an average ADKS score of 17.21 out of 30. However, participants showed a positive attitude toward dementia, as evidenced by a mean DAS score of 88 out of 140. Statistical analysis demonstrated significantly higher knowledge scores among employed individuals ( P  < .05), while females exhibited significantly higher attitude scores ( P  < .05). Participants with experience in geriatric clinical practice, dementia education or training, informal caregiving experience, and a desire to learn more about dementia also exhibited significantly higher knowledge and attitude scores ( P  < .05). Conclusion The study offers preliminary insights into the knowledge and attitudes toward dementia in the Jordanian population. The findings underscore the importance of continuing education and training to increase knowledge and understanding of dementia. Improving dementia care and support in Jordan requires enhancing knowledge and attitudes toward dementia. The study findings were presented to policymakers, with recommendations for strategic planning and the development of awareness programs. Future research can build upon these findings and promote evidence-based practices in dementia care and community awareness programs.